Respuesta :
Answer: -3y + 8z
Step-by-step explanation:
2x -2x = 0
-2y + - y= -3y
5z + 3z= 8z
-3y + 8z
The expression 2x − 2y + 5z − 2x − y + 3z is simplified as − 3y + 8z.
What is simplification?
Making anything easier to accomplish or comprehend, as well as making it less difficult, is the definition of simplification.
PEMDAS rule means for the Parenthesis, Exponent, Multiplication, Division, Addition, and Subtraction. This rule is used to solve the equation in a proper and correct manner.
The expression is given below.
⇒ 2x − 2y + 5z − 2x − y + 3z
Simplify the expression, then we have
⇒ 2x − 2y + 5z − 2x − y + 3z
⇒ 2x − 2x − 2y − y + 5z + 3z
⇒ 0 − 3y + 8z
⇒ − 3y + 8z
The expression 2x − 2y + 5z − 2x − y + 3z is simplified as − 3y + 8z.
More about the simplification link is given below.
https://brainly.com/question/12616840
#SPJ2